Leptochilus gracilis (Polypodiaceae), a new fern species from southeastern Yunnan, China based on morphological and molecular evidence - Liang, Zhen-Long; Shui, Yu-Min; Chen, Wen-Hong; Yu, Zhi-Yong; Zhang, Liang; Zhang, Li-Bing (Phytotaxa, 2020)
A new fern species, Leptochilus gracilis, is described and illustrated from southeastern Yunnan, China. Leptochilus gracilis is most similar to L. ellipticus. Compared with L. ellipticus, L. gracilis has a smaller habit with fronds less than 20 cm long, laminae with only one or two pairs of lobes, and midrib of lobes at angles of 45–60 degree with rachis. In contrast, L. ellipticus has a larger habit with fronds more than 30 cm long, laminae with (3–)4–9 pairs of lobes, and midrib of lobes at angles ca. 80–90 degree with rachis. A phylogenetic analysis based on four plastid markers confirmed the recognition of the new species and resulted in an isolated subclade of L. ellipticus clade.